1994
DOI: 10.1084/jem.180.6.2147
|View full text |Cite
|
Sign up to set email alerts
|

A genetically detoxified derivative of heat-labile Escherichia coli enterotoxin induces neutralizing antibodies against the A subunit.

Abstract: SummaryEscherichia coli enterotoxin (LT) and the homologous cholera toxin (CT) are A-B toxins that cause travelers' diarrhea and cholera, respectively. So far, experimental live and killed vaccines against these diseases have been developed using only the nontoxic B portion of these toxins. The enzymatically active A subunit has not been used because it is responsible for the toxicity and it is reported to induce a negligible titer of toxin neutralizing antibodies. We used sitedirected mutagenesis to inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 41 publications
(46 reference statements)
4
85
1
1
Order By: Relevance
“…An alternative approach to circumvent this problem is the use of genetically detoxified heat labile enterotoxins of E. coli LTK63 or non-toxic mutant cholera toxin CT S61F. 125,134,135 The challenge currently faced by several laboratories is to discover whether or not the promising results obtained in the animal model can be reproduced in humans.…”
Section: Vaccination Development For Clinical Use and Future Of The Hmentioning
confidence: 99%
“…An alternative approach to circumvent this problem is the use of genetically detoxified heat labile enterotoxins of E. coli LTK63 or non-toxic mutant cholera toxin CT S61F. 125,134,135 The challenge currently faced by several laboratories is to discover whether or not the promising results obtained in the animal model can be reproduced in humans.…”
Section: Vaccination Development For Clinical Use and Future Of The Hmentioning
confidence: 99%
“…One LT variant, named LT4, showed the same amino acid composition as the previously reported pLT, and in vivo and in vitro results indicated that this LT type has reduced toxicity with regard to the most ubiquitous LT1 and LT2 types (22). Of note, pLT has been used for definition of the LT tertiary structure and as a template for the generation of nontoxic or attenuated LT derivatives used as vaccine adjuvants (4,5,(7)(8)(9). In fact, during the last three decades, pLT and hLT were considered similar both with regard to their toxic effects and immunomodulatory activities in murine hosts, but no direct comparison of the two toxins has been reported so far.…”
Section: Enterotoxigenic Escherichia Coli (Etec)mentioning
confidence: 78%
“…To avoid the mucosal toxicity exhibited by the native toxin, different LT mutants with reduced toxic effect but partially preserved adjuvanticity were tested in the murine model (13,14). Among the several LT mutants generated under laboratory conditions, LTK63 and LTR72, with no or drastically reduced enzymatic activity, and LTR192G, lacking the trypsin cleavage site, have been intensively investigated as potential mucosal adjuvants in the mouse model (8,9,15).…”
Section: Enterotoxigenic Escherichia Coli (Etec)mentioning
confidence: 99%
See 1 more Smart Citation
“…While CT has been the standard for mucosal adjuvant activity, the toxicity of the A subunit has discouraged clinical use [174]. LT also has toxicity associated with its A subunit, but mutants with signifi cantly lower toxicity have been generated [175,176]. The mutants LTK63 and LTR72 have been shown to have potent activity in the generation of mucosal antibody in preclinical models against a variety of antigens when administered by oral, nasal [177], or transdermal routes [178] and appear ready for clinical testing [177].…”
Section: Historical Progressionmentioning
confidence: 99%